Fourteen-Year Patency of an Anterior Tibial Artery-Saphenous Vein Fistula in an Ambulatory Patient - Zerrin Pulathan; Gökalp Altun (Case Reports in Vascular Medicine)
Background. Ankle arteriovenous fistulas are the rarest vascular access type among lower extremity fistulas for hemodialysis patients with end-stage renal disease. Here, we present a case of a tibial-saphenous fistula that remained open for a long time despite a recurrent anastomotic aneurysm. Case Presentation. A 43-year-old female patient who had been undergoing hemodialysis via a right femoral tunnel catheter for six months was referred for recurrent catheter infection and a 4 cm pulsatile mass in the anterior aspect of the ankle. While she had been undergoing hemodialysis through a right tibial-saphenous fistula for fourteen years, hemodialysis continued after the fistula’s closure due to total occlusion of the great saphenous vein through the tunneled catheter. After balloon angioplasty to the right subclavian vein, we performed right upper extremity basilic vein transposition. Later, after starting adequate dialysis from the basilic vein fistula and removing the femoral catheter, we performed a resection of the anastomotic aneurysm in the right ankle and repaired the anterior tibial artery. Because this is the only ambulatory patient and the one with the longest patency of ankle arteriovenous fistulas in the literature and the only case in which the anterior tibial artery was used, the case is presented and discussed in light of the literature. Conclusion. Despite many complications and low patency rates reported in the literature, ankle vessels should be considered for autogenous vascular access in selected patients.